EFEKTIVITAS PELAYANAN PENCATATAN NIKAH DI KUA KECAMATAN BALIKPAPAN SELATAN SETELAH DIBERLAKUKANNYA INSTRUKSI DIRJEN BIMAS ISLAM NOMOR DJ.II/1 TAHUN 2015 - Shaleh Shaleh (Islamic Family Law, STAI Sangatta Kutai Timur, 2023)
The background of this research is the implementation of the Director General of Islamic Guidance No. DJ.II/1 the Year 2015 Instruction which deactivates the Assistant of Marriage Registrar or